Parameter matching and experiment of the combined cyclone separation and cylinder sieve cleaning system for rape combine harvester - Yuan, Jiacheng; Liao, Qingxi; Wan, Xingyu; Yang, Jia; Shu, Caixia (International Journal of Agricultural and Biological Engineering, 2024)
Existing rape combine harvester with a cyclone separation cleaning device has the challenge that the loss rate and the cleaning rate increase and decrease simultaneously. A cleaning process route was proposed, which involves the cyclone separation cleaning device removing light and tiny impurities, and the cylinder sieve device removing coarse and long impurities such as pod shells and short stems. A novel cleaning system combining the cyclone separation cleaning device and cylinder sieve cleaning devices was designed. The ranges of the structure and operation parameters for each component were analyzed based on kinematics and dynamic analysis. A four-factor five-level quadratic orthogonal test was carried out, in which the loss rate and cleaning rate were taken as the evaluation indexes. The velocity at the suction port, the rotation speed of the cylinder sieve, the screw pitch of the spiral blade and the diameter of the sieve hole were taken as the influencing factors. The orthogonal test results showed that the cleaning system performed best at a rotation speed of the winnower is 600 r/min, an airflow velocity at the suction port is 18.25 m/s, a rotation speed of the cylinder sieve is 87 r/min, a screw pitch of the spiral blade is 440 mm and a diameter of the sieve hole is 4.48 mm. At this time, the loss rate of the cleaning system is 3.22%, and the cleaning rate is 95.67%. Compared to the conventional cyclone separation cleaning device, the loss rate is reduced by 2.17% and the cleaning rate is increased by 1.05%. This study can provide a reference for the optimal cleaning system design for rape combine harvesters.Keywords: agricultural engineering, cleaning system, cyclone separation, cylinder sieve, rape combine harvesterDOI: 10.25165/j.ijabe.20241701.7739Citation: Yuan J C, Liao Q X, Wang X Y, Yang J, Shu C X. Parameter matching and experiment of the combined cyclone separation and cylinder sieve cleaning system for rape combine harvester. Int J Agric & Biol Eng, 2024; 17(1): 128-136.